Ownership structure and firm performance: the case of Indonesia - Lukviarman, Niki (Curtin University, 2004)
This study looks at the relationship between ownership structure, monitoring and firm performance. The research employed the agency theory hypothesised by Jensen and Meckling (1976) from the view of contractual relationships among various parties involved within a company. It presents a longitudinal study of the 161 non- financial publicly listed companies in the Jakarta Stock Exchange between 1994- 2000. This design enables a researcher not only to examine the effects of various governance variables on corporate performance, but also to examine the extent to which such relationships vary with changes in the general economic environment. This study reveals that only a small proportion of private-domestic Indonesian firms have a widely dispersed ownership structure. Viewed from the standpoint of traditional agency theory, the separation of ownership and control seems to work differently in Indonesia. In this country the agency problem is not between the owners and the managers, as in Anglo-Saxon countries, but may be between “strong” controlling shareholders and “weak” minority owners. The findings suggest a strong association between degrees of ownership concentration, owner involvement in supervisory/management board and the existence of family business groups. These factors are interdependent, and each of them relates cohesively to the others within the organisation. In this regard, the collectivism and higher power distance value dimensions that are dominant in Indonesian society also heighten such relationships. Inappropriate institutional, law and legal enforcement provide the means for the controlling shareholders to continue these practices, which insulate them from external interference, monitoring and supervision.Taken together, these findings support the view that national cultural features have a profound effect on the structure of national economies. The evidence corroborates the uniqueness of corporate governance practices in Indonesia, and the findings support the supremacy of controlling shareholders Further to the growing debate on the costs and benefits of controlling shareholders, the empirical findings of this study reveal that these shareholders are the source of the corporate governance problem rather than solution. In short, the most basic factor which inhibits the effectiveness of corporate governance implementation in Indonesia is the existence of powerful large shareholdings in the hands of a family. Governance reform, therefore, should address the corporate system by seeking to reduce the supremacy of these shareholders, and at the same time empower the other stakeholders. The findings also support the view of both the co-evolutionary and path-dependency theories in regard to factors that determine the pattern of ownership structure. The development of firms in Indonesia follows the path-dependence structure and, during this process, the firms’ environments will interact with and operate endogenous responses for environmental change. Such exogenous and endogenous forces shape the environment and trigger organisations to adapt in different ways so that they are able to survive.Thus, one would expect there to be different corporate governance systems within each country and any effort towards reforming such systems should consider factors specific to that country. This implies that governance reforms should be fully compatible with a country’s national culture, institutional, legal and business systems. Other variables, such as informal norms (social norms and cultural beliefs) and the political environment in a country should also be considered in the design of these reforms.